2019
DOI: 10.21763/tjfmpc.569484
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Physicians and Nurses Towards the Disabled and Awareness of Applications for the Disabled in a University Hospital

Abstract: Introduction: Population of the disabled is increasing worldwide and the disabled face with many limitations due to various social and physical obstacles. It is important that the practices that are made in order to provide the ideal health care service for the disabled are in compliance with the current legislation and that the attitudes of health personnel are positive.  The present study aims at determining the awareness of the physicians and nurses in a university hospital about the applications for the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 15 publications
1
7
2
5
Order By: Relevance
“…In our study, according to the marital status of the participants, the attitude of single individuals towards disabled individuals was found to be more favourable than married individuals (Table 2). Kılıç and Çıtıl (17) reported differently from our study, and found the marital status of the participants did not have a significant effect on the attitudes of the participants towards disabled individuals.…”
Section: Discussioncontrasting
confidence: 90%
See 4 more Smart Citations
“…In our study, according to the marital status of the participants, the attitude of single individuals towards disabled individuals was found to be more favourable than married individuals (Table 2). Kılıç and Çıtıl (17) reported differently from our study, and found the marital status of the participants did not have a significant effect on the attitudes of the participants towards disabled individuals.…”
Section: Discussioncontrasting
confidence: 90%
“…This result shows that healthcare professionals have positive attitudes towards people with disabilities. Kılıç and Çıtıl's study with physicians and nurses in performed in 2019 revealed a moderate positive attitude, similar to our study (17) . Sarı et al (16) reported that nursing students had positive attitudes towards disabled people.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations